Travel and translation in the early modern period - Di Biase, Carmine, 1959- (Approaches to translation studies, 2006)
The relationship between travel and translation might seem obvious at first, but to study it in earnest is to discover that it is at once intriguing and elusive. Of course, travelers translate in order to make sense of their new surroundings; sometimes they must translate in order to put food on the table. The relationship between these two human compulsions, however, goes much deeper than this. What gets translated, it seems, is not merely the written or the spoken word, but the very identity of the traveler. These seventeen essays--which treat not only such well-known figures as Martin Luther.